Os impactos dos sistemas de Enterprise Resource Planning (ERP) nas empresas do Polo Industrial de Manaus - Santos, Sebastião da Penha (Brasil, 2024)
The convergence of technology and management plays a central role in modern business dynamics. In this context, the adoption of Enterprise Resource Planning (ERP) technology has proven to be a transformative factor in business management. This study focuses on analyzing 'The Impacts of Enterprise Resource Planning (ERP) Systems on Companies in the Manaus Industrial Pole,' from the perspective of its managers. ERP systems emerge as an integration solution that covers a diverse range of organizational functions. Through a qualitative analysis of recent literature reviews and interviews with professionals from companies in various sectors of the Manaus Industrial Pole (PIM), the aim was to understand professionals' perceptions of the impacts of ERP systems. A semi-structured interview script was used to present and examine the effects of this technology in the specific context of the PIM.The data indicated that the implementation of ERP systems promoted operational efficiency by optimizing processes and minimizing redundancies. The availability of real-time information allowed for data-driven decision-making, providing a competitive advantage in a dynamic environment and offering relevant insights for managers, academics, and professionals seeking to understand how technological convergence is shaping business management in specific contexts. However, transformations resulting from ERP adoption do not occur without challenges. Adapting organizational processes, change management, and compliance with local regulations are crucial issues in the context of the Manaus Industrial Pole